Promoting Osteogenic Differentiation of Human Adipose-Derived Stem Cells by Altering the Expression of Exosomal miRNA. (1st July 2019) - Yang, Shude; Guo, Shu; Tong, Shuang; Sun, Xu
Abstract : Human adipose-derived stem cells (ADSCs) can release exosomes; however, their specific functions remain elusive. In this study, we verified that exosomes derived from osteogenically differentiated ADSCs can promote osteogenic differentiation of ADSCs. Furthermore, in order to investigate the importance of exosomal microRNAs (miRNAs) in osteogenic differentiation of ADSCs, we used microarray assays to analyze the expression profiles of exosomal miRNAs derived from undifferentiated as well as osteogenically differentiated ADSCs; 201 miRNAs were upregulated and 33 miRNAs were downregulated between the two types of exosomes. Additionally, bioinformatic analyses, which included gene ontology analyses, pathway analysis, and miRNA-mRNA-network investigations, were performed. The results of these analyses revealed that the differentially expressed exosomal miRNAs participate in multiple biological processes, such as gene expression, synthesis of biomolecules, cell development, differentiation, and signal transduction, among others. Moreover, we found that these differentially expressed exosomal miRNAs connect osteogenic differentiation to processes such as axon guidance, MAPK signaling, and Wnt signaling. To the best of our knowledge, this is the first study to identify and characterize exosomal miRNAs derived from osteogenically differentiated ADSCs. This study confirms that alterations in the expression of exosomal miRNAs can promote osteogenic differentiation of ADSCs, which also provides the foundation for further research on the regulatory functions of exosomal miRNAs in the context of ADSC osteogenesis.